DEVELOPMENT AND VALIDATION OF 3AB-ELISATEST-SYSTEM FOR DETECTION OF ANTIBODIES TO FMD VIRUS NONSTRUCTURAL PROTEINS IN BLOOD SERA FROM CATTLE AND SMALL RUMINANTS - A. S. Yakovleva; A. V. Kanshina; A. V. Scherbakov; Ye. S. Orlova (Ветеринария сегодня)
The 3AB-ELISA test-system for detection of antibodies to FMD virus nonstructural proteins in blood sera from cattle and small ruminants was validated. It was discovered that the reaction repeatability and reproducibility exceeded 90%, diagnostic specificity constituted 99,8%, diagnostic sensitivity came up to 96,6%. The high specificity and sensitivity of the 3AB-ELISA test-system was confirmed by international proficiency testings as far as FMD diagnostics and by routine diagnostic and monitoring studies.